Early detection and serial monitoring during chemotherapy-radiation therapy: Using T1 and T2 mapping cardiac magnetic resonance imaging - Tian, Yaotian; Wang, Teng; Tian, Liwen; Yang, Yucheng; Xue, Chen; Sheng, Wei; Wang, Cuiyan (Frontiers in Cardiovascular Medicine, 2023)
Purpose To confirm the ability of native T1 and T2 values in detecting and monitoring early myocardial injuries of chest radiotherapy in neoplasm patients. Materials and methods Fifteen participants received non-anthracycline chemotherapy and chest radiotherapy, and 30 age/gender-matched controls were enrolled in this prospective study. Cardiac magnetic resonance scans were performed within 2 days, 3 months, and 6 months after chest radiotherapy. Myocardial native T1 and T2 values were measured in irradiated and nonirradiated areas. Meanwhile, the parameters of left ventricular function and left ventricular myocardial strain were obtained. Results There were no significant differences in left ventricular function, native T1, T2, and strain between patients and controls before chest radiotherapy. In 15 participants who were followed up for 6 months, there was a significant change only in left ventricular ejection fraction (LVEF) among baseline and the first follow-up (P = 0.021), while the adjusted P-value was higher than 0.05 after Bonferroni correction, as well as other parameters. Native T1 values were elevated at 3 and 6 months in irradiated areas compared with baseline (1,288.72 ± 66.59 ms vs. 1,212.51 ± 45.41 ms; 1,348.01 ± 54.16 ms vs. 1,212.51 ± 45.41 ms; P < 0.001 for both). However, T2 values only changed at 3 months in irradiated areas compared with baseline (44.21 ± 3.35 ms vs. 39.14 ± 1.44 ms; P = 0.006). Neither the native T1 nor T2 values changed in nonirradiated areas during the follow-up period (all P > 0.05). There were no significant differences in strain changes during the follow-up period (all P > 0.05). Conclusion Native T1 and T2 values elevated at 3 months after chest radiotherapy, whereas LVEF showed no significant change during the 6-month follow-up.